Electrochemically active site-rich nanocomposites of two-dimensional materials as anode catalysts for direct oxidation fuel cells: new age beyond graphene. Issue 13 (7th June 2021) - Baruah, Kashmiri; Deb, Pritam
Abstract : This review highlights recent advances in the development of efficient and durable anode catalysts based on new emerging 2D materials beyond graphene. Abstract : Direct oxidation fuel cell (DOFC) has been opted as a green alternative to fossil fuels and intermittent energy resources as it is economically viable, possesses good conversion efficiency, as well as exhibits high power density and superfast charging. The anode catalyst is a vital component of DOFC, which improves the oxidation of fuels; however, the development of an efficient anode catalyst is still a challenge. In this regard, 2D materials have attracted attention as DOFC anode catalysts due to their fascinating electrochemical properties such as excellent mechanical properties, large surface area, superior electron transfer, presence of active sites, and tunable electronic states. This timely review encapsulates in detail different types of fuel cells, their mechanisms, and contemporary challenges; focuses on the anode catalyst/support based on new generation 2D materials, namely, 2D transition metal carbide/nitride or carbonitride (MXene), graphitic carbon nitride, transition metal dichalcogenides, and transition metal oxides; as well as their properties and role in DOFC along with the mechanisms involved.